Strategi Coping Stress dalam Menyelesaikan Skripsi pada Mahasiswa Psikologi Angkatan 2020 Universitas Negeri Padang - Darussalam, Darussalam; Alfurqan, Alfurqan (Lembaga Yasin AlSys, 2025)
This study aims to examine the stress coping strategies employed by 2020 Psychology students at Universitas Negeri Padang in managing academic pressure during thesis writing. Academic workload, time constraints, and interpersonal challenges, such as difficulties in communication with supervisors and social expectations are identified as significant stressors. Coping strategies are considered vital mechanisms for managing these pressures. The study is grounded in Lazarus and Folkman's (1984) coping theory, which categorizes strategies into two main types: problem-focused coping and emotion-focused coping. A qualitative approach was employed, using a questionnaire instrument based on Lazarus and Folkman's coping dimensions. The research involved 30 active students currently working on their theses. The results indicate that the majority of respondents predominantly used problem-focused coping strategies, such as creating schedules, seeking additional information, consulting with supervisors, and forming study groups. In contrast, emotion-focused coping strategies, such as praying, withdrawing, or distraction were used less frequently. The study concludes that the transactional model of stress and coping remains highly relevant in the context of higher education and emphasizes the need for psychological and academic support programs to help students adaptively manage stress throughout the thesis-writing process.